Translocation alters the activation rate of a trypanosome surface antigen gene. - Laurent, M (1984)
We report here the characterization of the gene coding for AnTat 1.13, a very late variable antigen type (VAT) from Trypanosoma b. brucei. This gene is chromosome-internal and it is activated by the duplicative mechanism. Like in another case of late VAT expression (1), its expression-linked copy (ELC) is flanked by "companion" sequences. It was possible to convert the late expression of this VAT into an early one, by changing the location of the gene in the genome. This has been achieved by selecting an AnTat 1.6 clone among heterotypes arising in the AnTat 1.13 cloned population. Indeed, this particular derivation leads to the conservation of the AnTat 1.13 ELC as a new telomeric member of the gene family, and this conserved ELC (or ex-ELC) appears to be preferentially activable. The telomeric position and other factors possibly involved in early or late antigen gene expression are discussed; in this respect, we propose that some antigen genes are rarely activated because their duplicative transposition requires the presence, in the expression site, of "companion" sequences only shared by a limited number of other genes.